Liquidity and Profitability Effects on Stock Prices Mediated by Trading Volume Activity - Triwulandari, Ratna; Sodik, M.; Alfiana, Alfiana (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the effects of liquidity and profitability on stock prices and examines whether Trading Volume Activity (TVA) mediates these relationships in technology-sector firms listed on the Indonesia Stock Exchange during the 2022–2024 post–tech winter period. The research adopts an explanatory quantitative approach using secondary panel data derived from published annual financial statements and official trading records. From a population of 47 firms included in the IDXTECHNO index, 24 companies were selected through purposive sampling, resulting in 72 firm-year observations. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4, and hypothesis testing was conducted through bootstrapping procedures. The findings indicate that liquidity, proxied by the Current Ratio, has a negative and significant effect on stock prices, while profitability, measured by Return on Assets, has a positive and significant influence. Liquidity does not significantly affect TVA, whereas profitability positively increases trading activity. Furthermore, TVA has a negative and significant effect on stock prices. Mediation testing shows that TVA does not mediate the relationships between liquidity, profitability, and stock prices. The structural model demonstrates limited explanatory power, suggesting that stock price variation is only partially explained by the proposed variables. Overall, the results imply that stock price formation in technology firms during the post–tech winter phase is driven primarily by direct fundamental performance, particularly profitability, rather than by trading activity mechanisms. These findings support Portfolio Theory and Signaling Theory under heightened market uncertainty.